Health Literacy, Occupational Health and Safety Factors and Quality of Life of Municipal Waste Collectors in the Northeast of Thailand (Indian Journal of Public Health Research & Development, 2020)
Waste collectors usually expose to several occupational health and safety risks which may affect theirhealth and wellbeing. Health literacy might help reducing occupational harms. Our aims were to assessthe health statusand to determine the influence of health literacy (HL) and occupational health and safety(OHS) factors on quality of life (QOL) of local administration organization waste collectors in Thailand.This cross-sectional study was conducted among 529 participants who were recruited by using a multistagerandom sampling from local administration organizations in 4 provinces of the Northeast of Thailand. A selfadministeredstructured questionnaire was used to assess OHS factors, HL, socioeconomic status (SES) andQOL. The Generalized Linear Mixed Model (GLMM) was used to determine the association between OHS,HL and QOL when controlling for other covariates. 62.95% of the participants reports as had good healthstatus. However, 51.04% had musculoskeletal disorders (MSDs), 36.37% had work related injuries and20.04% had chronic disease. Only 42.53% had adequate to excellence level of HL and the same proportionhad good QOL. The GLMM analysis indicated factors that were significantly associated with good qualityof life when controlling the effect of regions of municipal waste collectors in the Northeast of Thailand were:did not have MSDs, had adequate to excellence levels of health literacy, had low level of stress related withsocial support on work, had higher level of education, had high level of knowledge on garbage collectionwork, had low stress related with job security. Less than half of municipal waste collection workers hadgood QOL. HL, free from MSDs, knowledge about waste collection, low levels of stress on job security, andsocial support on job had influence on QOL as well as educational attainment.
Keywords: Health literacy, Municipal waste collectors, Occupational health and safety, Quality of life.